Renal Denervation Update From the International Sympathetic Nervous System Summit: JACC State-of-the-Art Review - Kiuchi, Márcio G.; Esler, Murray D.; Fink, Gregory D.; Osborn, John W.; Banek, Christopher T.; Böhm, Michael; Denton, Kate M.; DiBona, Gerald F.; Everett, Thomas H.; Grassi, Guido; Katholi, Richard E.; Knuepfer, Mark M.; et al. (Journal of the American College of Cardiology, 2019)
Three recent renal denervation studies in both drug-naïve and drug-treated hypertensive patients demonstrated a significant reduction of ambulatory blood pressure compared with respective sham control groups. Improved trial design, selection of relevant patient cohorts, and optimized interventional procedures have likely contributed to these positive findings. However, substantial variability in the blood pressure response to renal denervation can still be observed and remains a challenging and important problem. The International Sympathetic Nervous System Summit was convened to bring together experts in both experimental and clinical medicine to discuss the current evidence base, novel developments in our understanding of neural interplay, procedural aspects, monitoring of technical success, and others. Identification of relevant trends in the field and initiation of tailored and combined experimental and clinical research efforts will help to address remaining questions and provide much-needed evidence to guide clinical use of renal denervation for hypertension treatment and other potential indications.
CRIS-Team Scopus Importer:2019-06-18
Keywords: blood pressure; cardiovascular disease; hypertension; renal denervation; sympathetic nervous system